An in vivo microdialysis characterization of the transient changes in the interstitial dialysate concentration of metabolites and cytokines in human skeletal muscle in response to insertion of a microdialysis probe. Issue 2 (February 2015) - Carson, Brian P.; McCormack, William G.; Conway, Clare; Cooke, John; Saunders, Jean; O'Connor, William T.; Jakeman, Philip M.
Highlights MD catheterisation of skeletal muscle causes a perturbation to tissue homeostasis. Carnosine, glutamine and taurine dialysate concentrations are elevated for up to 2 h. A sustained elevation of IL-6 and IL-8 dialysate concentrations persist for 7 h. This response occurs during apparent stable glucose and lactate metabolism.